2020
DOI: 10.1371/journal.pone.0243704
|View full text |Cite
|
Sign up to set email alerts
|

Cyberchondria in the age of COVID-19

Abstract: The global epidemic of (mis)information, spreading rapidly via social media platforms and other outlets, can be a risk factor for the development of anxiety disorders among vulnerable individuals. Cyberchondria can be a vulnerability factor for developing anxiety in a pandemic situation, particularly when the Internet is flooded with (mis)information. The aim of our study was to examine how cyberchondria is related to changes in levels of COVID-19 concern and safety behaviours among persons living in Croatia d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(102 citation statements)
references
References 30 publications
3
84
1
4
Order By: Relevance
“…Many clinical studies have recommended shifting from the traditional specific disorder–focused approach toward a transdiagnostic treatment as an alternative approach. Despite some scholars’ assertions [ 77 ], the findings of this study do not justify cyberchondria as a transdiagnostic condition. However, the transdiagnostic treatments or application of the relative modules may be effective in treatment for cyberchondria.…”
Section: Discussioncontrasting
confidence: 99%
“…Many clinical studies have recommended shifting from the traditional specific disorder–focused approach toward a transdiagnostic treatment as an alternative approach. Despite some scholars’ assertions [ 77 ], the findings of this study do not justify cyberchondria as a transdiagnostic condition. However, the transdiagnostic treatments or application of the relative modules may be effective in treatment for cyberchondria.…”
Section: Discussioncontrasting
confidence: 99%
“…This condition has certainly been exacerbated during the pandemic, even more so by the spread of ambiguous information. A study conducted in Croatia ( Jovic-Begic et al, 2020 ) revealed that high cyberchondria levels and high levels of preoccupation with COVID-19 were associated with intense avoidance behavior, as was evidenced in our research work by the patients’ missing medical visits due to the fear of leaving the home. Such a concept would also explain the reason SI and PPD were associated in our study with a greater number of daily hours spent seeking information.…”
Section: Discussionsupporting
confidence: 70%
“…This may be because of the prolonged period of home quarantine and restrictions on face-to-face contact; because of which, people may undergo through greater distress and seek an escape through online activities (55). People's insecurity and anxiety for the disease can push them toward compulsive checking for information online which further escalate their anxiety, creating a vicious cycle of cyberchondria that is hard to stop (56,57).…”
Section: Prevalence Of Cyberchondria During Covid-19mentioning
confidence: 99%